STRATEGIC PROGRAM FOR BUFFALO DEVELOPMENT IN SOUTH SULAWESI: AN IDEA AND CONCEPTS - Said, Syahruddin (Proceeding Buffalo International Conference, 2013)
The objective of this study was to determine the strategic program for buffalo development in South Sulawesi. The study was a thought of idea and concepts to create programs and strategic activities for buffalo development by using SWOT analysis that preceded the determination of the internal and external factors. Based on the results of SWOT analysis, the strength map for buffalo development in South Sulawesi was in quadrant I (aggressive), this indicated that by utilizing the opportunities and minimizing the threats, buffalo development in South Sulawesi was able to improve faster and making center of development buffalo in Indonesia. Operational policy strategy in determining the program of activities, were: (1) take advantage of the ability of buffalo convert low-quality feed to fulfill the demand for meat;(2) to intensify AI in order to improve the birth that the demand for meat can be fulfilled, (3) utilizing buffalo ability to convert low-quality feed to reduce importation of meat, and (4) to intensify AI in order to improve the birth so that meat imports could be reduced.